How to build Theories of Change for transdisciplinary research: Guidance and considerations - Claus, R.; Davel, R.; Heykoop, C.; Pinto, D.; Belcher, B.M. (Oekom Publishers GmbH, 2023)
Transdisciplinary research (TDR) aims to solve problems in complex systems by drawing from a range of methods and expertise to contribute to change processes. Theories of Change (ToCs) are well-suited to support TDR design and implementation, but they rarely achieve their full potential. In practice, ToCs are often compromised by insufficient engagement with the context, weak theoretical bases, poor articulation, and a lack of iteration. This paper presents a process for ToC design based on the authors’ experience facilitating ToC development for research planning and evaluation. We illustrate the process using an in-progress TDR example on patient-oriented cancer care research. The approach begins by framing the social and research problems and then identifies activities and outputs, key actors, outcomes, and underlying causal assumptions. Skilled facilitation and strong conceptual familiarity are key to effectively mobilize ToC concepts into a cohesive and testable model to refine a strategy with TDR stakeholders. Key considerations and resources are offered to enhance ToC development planning and facilitation.